Emotional Intelligence in Insurance Leaders For Managing Business Communication with Generation Z - Dwiastuti, Winda; Basir, Yulinda; Febrianno Boer, Rino (Jurnal Spektrum Komunikasi, 2024)
Modern business landscape, including the insurance industry, demands effective leadership to navigate the complex interpersonal dynamics, especially when working with Gen Z as the newest generation that enters the workplace. Gen Z employees, with their unique expectations and communication styles, seek leaders who offer transparency, authenticity, and emotional connection. This study explores the significant role of emotional intelligence (EI) in achieving leadership success within insurance companies. Emotional intelligence is increasingly recognized as a key factor in leadership effectiveness, influencing how leaders build relationships, make strategic decisions, and inspire their teams. Given the competitive nature of the insurance industry and its technological advancements, leaders must adeptly manage a multigenerational workforce and adapt to new challenges. This qualitative research explores how insurance leaders utilize EI to engage Generation Z, who prioritize diversity, collaboration, and flexible leadership. By understanding Generation Z's unique communication preferences, emotionally intelligent leaders enhance organizational performance and employee satisfaction. Drawing on current literature and interviews with leaders from an insurance company in Indonesia, this study finds that leaders with high emotional intelligence significantly boost employee engagement, satisfaction, and productivity. The findings emphasize the importance of integrating emotional intelligence into leadership practices to ensure resilience and competitiveness in the market, benefiting organizations by bridging generational gaps and empowering Gen Z employees.